The genital tract microbiome: bridging the gap between hype and clinical reality - Vieira-Baptista, Pedro (Brazilian Journal of Sexually Transmitted Diseases, 2024)
In the last years there has been a huge interest in the study of the human microbiome, and the genital tract one has been no exception. However, we still fail to fully understand the normal and abnormal genital tract microbiome. Despite the increasing knowledge, the diagnosis of vaginitis is mostly empirical and many interventions, such as the use of probiotics, are not supported by good quality evidence.